History of universities. Volume XXIX/2 / Mordechai Feingold and Alexander Broadie. - Feingold, Mordechai; Broadie, Alexander (Oxford University Press, 2017)
This volume contains the customary mix of learned articles and book reviews which makes this publication such an indispensable tool for the historian of higher education. This special issue, guest edited by Alexander Broadie, particularly focuses on seventeenth-century Scottish philosophers and their philosophy.